Studi Tentang Keamanan dan Keselamatan Pengunjung Hubungannya dengan Citra Destinasi (Studi Kasus Gembira Loka Zoo) - suharto suharto (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2016)
Image is one of the essential elements for a tourist destination and a description of the impression of a tourist destination. A good image will motivate tourists to visit a destination. The research uses Gembira Loka Zoo as an object. The purpose of this research was to identify the factors related to the image of a destination, especially in the management of the security and safety of visitors conducted by travel managers Gembira Loka Zoo. The method used in this research related to the security and safety of visitors is descriptive Research is Descriptive to investigate population and samples. The population is tourists who visit Gembira Loka Zoo and the samples are 100 respondents. In addition, researchers also conduct observation, Questionnaires and documentation in the data collection. The analysis technique used there are several steps that include the instrument of accession test, validity, reliability, hypothesis, coefficient of determination and F test and T. The result showed a Gembira Loka Zoo has a good image of tourist mind and the result showed a significant correlation between Gembira Loka Zoo Image and tourist visiting motivation. With this research is expected that manager can improve all of the aspects of Gembira Loka Zoo so it can be motivate tourist to visit.